ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU AMPAS RUMPUT LAUT MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) UNTUK MENINGKATKAN EFISIENSI BIAYA PADA PT JIMAT PERKASA FARM TAHUN 2023 - M. Selamet Riyadi; Achmad Misbah (Bajang Institute, 2024)
Optimal raw material inventory is an important factor in the smooth production process of a company. This raw material can be controlled using certain methods, one of which is the Economic Order Quantity (EOQ) method which has a better level of calculation accuracy than conventional methods. The aim of the research is to examine more deeply the use of the Economic Order Quantity (EOQ) method in controlling raw material inventories and to increase inventory cost efficiency at PT Jimat Perkasa Farm. The object of this research is the amount of use, the amount of raw material inventory as well as ordering costs and storage costs for raw materials. The results of the research using the EOQ method calculation for the most economical ordering of seaweed pulp raw material in 2023 were 1,369 tons with an ordering frequency of 2 times. Safety stock of raw materials for seaweed dregs in 2023 is 102 tons. With a lead time of 1 days, it can be seen that the reorder point for seaweed pulp raw material in 2023 will be 110 tons. The total inventory costs for raw materials incurred by PT Jimat Perkasa Farm based on the results of EOQ calculations, it turns out that the total inventory costs are smaller than the total inventory costs that have been calculated by the company. The total cost of seaweed pulp supplies that must be spent by PT Jimat Perkasa Farm in 2023 using the EOQ method is IDR 2,190,890